2018
DOI: 10.1242/dev.164657
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cis-acting elements mediate targeting and clustering of Drosophila polar granule mRNAs

Abstract: Specification and development of Drosophila germ cells depend on molecular determinants within the germ plasm, a specialized cytoplasmic domain at the posterior of the embryo. Localization of numerous mRNAs to the germ plasm occurs by their incorporation, as single-transcript ribonucleoprotein (RNP) particles, into complex RNP granules called polar granules. Incorporation of mRNAs into polar granules is followed by recruitment of additional like transcripts to form discrete homotypic clusters. The cis-acting l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 51 publications
1
53
0
Order By: Relevance
“…S6 " type="url"/> ). These observations are echoed by other reports of homotypic mRNA spatial separation within germ granules ( Eagle et al, 2018 ; Trcek et al, 2015 ) and suggest a complex organization to granules and the mRNAs they contain.…”
Section: Resultssupporting
confidence: 49%
“…S6 " type="url"/> ). These observations are echoed by other reports of homotypic mRNA spatial separation within germ granules ( Eagle et al, 2018 ; Trcek et al, 2015 ) and suggest a complex organization to granules and the mRNAs they contain.…”
Section: Resultssupporting
confidence: 49%
“…Curiously, we noticed transcripts did not mix homogenously within P granules but occupied discrete regions within granules depending on their type. For example, clu-1 mRNA typically surrounded a chs-1 mRNA core ( 9/38 separation within germ granules [Eagle et al, 2018, Trcek et al, 2015 and suggest a complex organization to granules and the mRNAs they contain.…”
Section: Quantification Strategies To Characterize Mrna Patterningmentioning
confidence: 99%
“…However, it has recently been shown that in Drosophila germ granules, formed at the egg’s posterior cytoplasm (germ plasm) referred to as polar granules, RNA molecules form homotypic clusters which contain multiple molecules of the same RNA species 7,8 . Further studies provided evidence that these homotypic RNA clusters are built up in the granules, starting from single RNA molecules, by a continuous seeding mechanism, which involves these RNAs’ 3’UTR elements responsible for RNA targeting to and clustering within the granules 9,10 . These studies provided important insights into RNA assembly in the polar granules.…”
Section: Introductionmentioning
confidence: 99%